Multiple post‐domestication origins of kabuli chickpea through allelic variation in a diversification‐associated transcription factor. Issue 4 (19th May 2016) - Varma Penmetsa, R.; Carrasquilla‐Garcia, Noelia; Bergmann, Emily M.; Vance, Lisa; Castro, Brenna; Kassa, Mulualem T.; Sarma, Birinchi K.; Datta, Subhojit; Farmer, Andrew D.; Baek, Jong‐Min; Coyne, Clarice J.; Varshney, Rajeev K.; et al.
Summary: Chickpea ( Cicer arietinum ) is among the founder crops domesticated in the Fertile Crescent. One of two major forms of chickpea, the so‐called kabuli type, has white flowers and light‐colored seed coats, properties not known to exist in the wild progenitor. The origin of the kabuli form has been enigmatic. We genotyped a collection of wild and cultivated chickpea genotypes with 538 single nucleotide polymorphisms (SNPs) and examined patterns of molecular diversity relative to geographical sources and market types. In addition, we examined sequence and expression variation in candidate anthocyanin biosynthetic pathway genes. A reduction in genetic diversity and extensive genetic admixture distinguish cultivated chickpea from its wild progenitor species. Among germplasm, the kabuli form is polyphyletic. We identified a basic helix–loop–helix (bHLH) transcription factor at chickpea's B locus that conditions flower and seed colors, orthologous to Mendel's A gene of garden pea, whose loss of function is associated invariantly with the kabuli type of chickpea. From the polyphyletic distribution of the kabuli form in germplasm, an absence of nested variation within the bHLH gene and invariant association of loss of function of bHLH among the kabuli type, we conclude that the kabuli form arose multiple times during the phase of phenotypic diversification after initial domestication of cultivated chickpea.